Writing Difficulties Faced by the Grade Eleven Students of Senior High School - Melinda Maria Korban; Jamiluddin; Budi; Sudarkam R. Mertosono (Institut Agama Islam Negeri Palopo, 2024)
This study was invertigated what kinds of writing difficulties faced by eleven grade students of SMA Negeri 1 Bolano. The aims of this study to find out kinds of the writing difficultie in descriptive paragraph. This research used a descriptive qualitative design to exporing the data. Student’ assignment from the teacher as the instrument of the data. five types of difficulties writing in descriptive paragraph as the finding in this research The difficulty classfie are spelling, capitalization, grammatical, vocabulary, and punctuation. From the data, the resercher found that the most frequent difficult made by students in decriptive pragraph is spelling ( twelve errors). It indicates that the students lack understading of how write the correct word. In light of the limitations identified in this study, It is recommended for future researchers who attempt the same case of this research to develop deeply the difficulties in writing descriptive paragraph to enhance the available references. Additionally, employing alternative to data collection methods, such as interviews and questionnaires, would yield more comprehensive insights into the specific factors contributing to the observed of the difficult and errors of writing descriptive paragraph.